2019
DOI: 10.1111/jdi.12986
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and pathways in diabetic nephropathy by bioinformatics analysis

Abstract: Aims/Introduction The aim of the present study was to identify candidate differentially expressed genes ( DEG s) and pathways using bioinformatics analysis, and to improve our understanding of the cause and potential molecular events of diabetic nephropathy. Materials and Methods Two cohort profile datasets ( GSE 30528 and GSE 33744) were integrated and used for deep analysis. We sorted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…In lupus, bioinformatics analysis revealed that CD38 and CCL2 are hub macrophage-related genes [8]. Additionally, EST1 may be a drug target for diabetic nephropathy treatment [9]. Currently, only a few bioinformatics analyses have been performed on IgAN; its critical associated genes and interactions have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In lupus, bioinformatics analysis revealed that CD38 and CCL2 are hub macrophage-related genes [8]. Additionally, EST1 may be a drug target for diabetic nephropathy treatment [9]. Currently, only a few bioinformatics analyses have been performed on IgAN; its critical associated genes and interactions have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…WGCNA was performed in an independent study of large number of samples of multiple kidney diseases, avoiding the heterogeneity among different studies caused by a comprehensive analysis of multiple GEO datasets. Different from the analysis of DEGs [14][15][16], the genome-wide transcriptional co-expression network analysis has provided an unbiased description of gene expression network in DN. A gene module speci c for DN was identi ed re ecting the unique pathogenesis of DN.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, VSIG4-related EMT was reported in renal cells as well as cancer metastasis [ 8 , 9 ]. Moreover, VSIG4 is upregulated in diabetic kidney disease, as indicated by bioinformatics analysis [ 10 ]. However, the precise role of VSIG4 in the diabetic milieu is still unclear.…”
Section: Introductionmentioning
confidence: 99%